Cashew apple bagasse lignin as support for immobilization of lipase B from Candida antarctica - Serpa, Juliana de França (2020)
Cashew apple (Anacardium occidentale L.) is a tropical pseudofruit with an outstanding economic role due to the cashew apple nut exportation. The industry of juice from cashew apple produces 15% (w/w) of bagasse, and this material is composed of cellullose, hemicelulose and lignin. Its structure is highly recalcitrant to microbial and enzymatic biotransformation, thus limiting its use and making its conversion into value-added products not economically feasible. So, the pretreatments are needed to disrupt the recalcitrant structures of the lignocellulosic material to increase the digestibility of the material prior to the conversion into value-added product. During the pretreatment of cashew apple bagasse, lignin is discarded and becomes a co-product. Though, it is a potential raw for production of different materials. In this context, this research aimed to extract and characterize lignin from CAB (Cashew Apple Bagasse), be used a new material. Pretreatment conditions for lignin extraction were studied from different hydrolysates obtained by diluted acid (A), acid/alkali (AA) and alkaline hydrogen peroxide (AHP) pretreatments. Lignin removals through AA and AHP pretreatments were 98.0% and 96.9%, respectively, achieving high extraction yield, and lignins with higher thermal stability. The lignina AA was chosen for the next steps of this study. Novel magnetite-lignin composite materials were synthesized using the by-product lignin from by AA pretreatment, extracted from CAB and nanoparticles of magnetite (Fe3O4), well-known for its nontoxicity and magnetic properties. This material, named MNs/Lig, was used as support for the immobilization of Lipase B from Candida antarctica (CAL-B), aiming to obtain an active and stable biocatalyst and with easy recovery of the reactional medium. The MNs/Lig supports and biocatalysts produced were characterized by Fourier Transform Infrared spectroscopy (FTIR), X-ray diffraction (XRD), Vibrating Sample Magnetometer (VSM), Thermogravimetric analysis (TGA), Scanning Electron Microscopy (SEM). The biocatalysts prepared were used in evaluated for the synthesis of esters using oleic acid as substrate and ethyl alcohol (1:1) and 2-ethyl-1-hexanol (1:1) as alcohol. The conversions obtained were 88.2% and 76.7% using 2-ethyl-1-hexanol and ethyl alcohol, respectively, being evaluating 5 cycles of reuse and it did not observe loss catalyst. Then, this new strategy to obtain a biocatalyst from synthesized hybrids (MNs/Lig) may be a promising carrier for enzymatic immobilization of lipases, in addition to being considered environmentally benign, aiming its use in reactions of industrial interest.